Citrus - Research, Development and Biotechnology 2021
DOI: 10.5772/intechopen.96873
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Applications for the Antioxidant Sensing in Food Samples Such as Citrus and Its Derivatives, Soft Drinks, Supplementary Food and Nutrients

Abstract: Although there are many definitions of antioxidants, the most general description; antioxidants are carried a phenolic function in their structure and prevent the formation of free radicals or intercept from damage to the cell by scavenging existing radicals. Moreover, they are one of the most effective substances that contain essential nutrients for healthy individuals. The importance of these antioxidants, which have an incredible effect on the body and increase the body’s resistance, is increasing day by da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 95 publications
(28 reference statements)
1
0
0
Order By: Relevance
“…The reversible nature is due to the twoelectron redox process of key diphenolic antioxidants, such as caffeic and chlorogenic acid to their quinone forms. These values are in good agreement with similar studies performed by Yildirim [27,[31][32][33][34]38,40,41,[43][44][45]48,49,[109][110][111]. Despite the differences in pH within the different studies, the values presented here are within the range of values reported elsewhere.…”
Section: Cyclic Voltammetrysupporting
confidence: 92%
“…The reversible nature is due to the twoelectron redox process of key diphenolic antioxidants, such as caffeic and chlorogenic acid to their quinone forms. These values are in good agreement with similar studies performed by Yildirim [27,[31][32][33][34]38,40,41,[43][44][45]48,49,[109][110][111]. Despite the differences in pH within the different studies, the values presented here are within the range of values reported elsewhere.…”
Section: Cyclic Voltammetrysupporting
confidence: 92%